Produção de sementes, de mudas em viveiro e cultivo a campo de Acca sellowiana (O. Berg) Burret: uma abordagem técnica e econômica - Tonetto, Thaíse da Silva (2018)
A. sellowiana is a native species that is destined for multiple use, such as consumption of flowers and fruits in natura or processed, manufacture of moirões, firewood, charcoal, landscaping, reforestation, enrichment of degraded areas, still presenting pharmaceutical and medicinal properties. Thus, the general objective of this research was to establish adequate techniques for the production of A. sellowiana seeds and seedlings, as well as to evaluate production costs and economic profitability. The specific objectives will be considered in five chapters, organized as follows: Chapter I - Describe for A. sellowiana: a) the morphometry of fruits and seeds; b) the germination morphology; c) the most suitable substrate; d) the place of storage of seeds and; e) the price of the kilo of seeds; Chapter II - Verify the growth of seedlings produced in nurseries; Chapter III - Characterize the best irrigation blade for the production of seedlings; Chapter IV - Evaluate the costs of seedling production against different substrate volumes and nursery fertilizations, as well as the financial implications. In addition, to measure and to ponder the costs involved in the productive process of seedlings arranged in different irrigation slides and Chapter V - To evaluate the survival and the growth of the seedlings in the field. The morphometric evaluation of fruits of Acca sellowiana allowed to establish the exact moment of collection and the measurement of seed biometry, which have medium dimensions, made it possible to know the strategies for the species' perpetuation. In the germination of A. sellowiana seeds the substrates can be used: on and between vermiculite, on and between blotting paper, on and between and filter and, on sand. Seed storage is feasible in a dry and cold room or a dry and cold room with relative humidity between 49 and 55% and a temperature between 7.5 and 18 ºC, despite the reduction of about 25% of the germination potential after 2 years of storage. There should be more investment in the storage of Acca sellowiana seeds, in order to guarantee the supply of seeds in years with possible seasonality of fruiting. Concerning the substrate and nutrient volume demand, the requirement of the species, with the best growth in a 180 cm³ container type receptacle and a fast release fertilizer (NPK and micronutrients) increased by 100%, was associated with cover fertilization. Studies with this approach should be carried out in parallel with cost analysis and economic feasibility. The 8 mm fixed irrigation blade provided adequate growth. Studies involving irrigation blades may provide a better guarantee of the successful production of seedlings in nurseries, with subsequent field monitoring, whose cost composition should be known and analyzed financially. Planting in the field of seedlings indicated that the species should be conducted in a larger volume of substrate (180 cm³) and planted with a height greater than 20 cm. Due to the low planting survival rate, the conduction must be carried out in another location with different conditions in relation to the study site, in order to correct and/or confirm the survival of Acca sellowiana plants.